ANALISIS RISIKO PEMBIAYAAN DI UNIT PENGELOLA KEGIATAN SYARIAH TUJUAH SARUMPUN NAGARI BIARO GADANG KECAMATAN AMPEK ANGKEK KABUPATEN AGAM - Rahmayani Rahmayani; Yuwarman Mansur (Fakultas Ekonomi dan Bisnis, Universitas Wiraraja Madura, 2025)
The Activity Management Unit (UPK) is a sustainability program from PNPM Mandiri in Rural Areas which is managed independently by village officials. This UPK provides loans or financing for the community that is used for capital or for other needs. The purpose of this study is to ascertain the financing risk at UPK Syariah Tujuah Sarumpun and how to mitigate such risk. The descriptive qualitative research approach is the one that is employed. Primary and secondary data are the types and sources of information that are utilized. This study used documentation, interviews, and observation as data gathering methods. The Miles and Huberman model's data analysis methodology—which includes data reduction, data presentation, and conclusion-making or data verification—is applied. According to the analysis, the findings of this study include several causes of problematic financing at UPK Syariah Tujuah Sarumpun namely economic factors, environmental factors and non-natural disaster factors. Risk mitigation carried out by UPK is with collateral or collateral. The strategy used by UPK to reduce problematic financing is by 5C analysis. The act of settlement of problem financing carried out by UPK is by conducting a direct review of the financing group and by rescheduling.